Microfluidic Ionic Liquid Dye Laser - Han Zhang; Chen Zhang; Seyedmohsen Vaziri; Fariba Kenarangi; Yuze Sun (IEEE Photonics Journal, 2021)
In this work, by utilizing ionic liquid as the gain medium solvent, which is a new category of materials, we demonstrated a droplet-based dye laser system in a co-flowing microfluidic device. We characterized the droplet laser system and achieved a lasing threshold of 40.1 μJ/mm2. Owning to the unique properties of ionic liquids, such as negligible vapor pressure and good thermal and chemical stability, they offer great potentials for the development of on-chip light sources, tunable optofluidic devices, and sensitive biochemical analysis.